Gut Microbiota and Its Role in Obesity and Metabolic Syndrome: A Narrative Review - Pączek, Adrian Jan; Kowalczyk, Aleksandra; Staniszewska, Wiktoria; Dyczek, Paweł; Hofman, Julia (Journal of Education, Health and Sport, 2025)
Background. Obesity and metabolic syndrome represent major global health challenges, with steadily increasing prevalence worldwide. Beyond caloric intake and physical activity, the gut microbiota has emerged as an important modulator of host metabolism and metabolic homeostasis. Objective. To summarize current evidence regarding the role of gut microbiota in obesity and metabolic syndrome and to discuss potential therapeutic interventions targeting the microbiota. Methods. This narrative review was based on a literature search in PubMed using the following keywords: gut microbiota, obesity, metabolic syndrome, probiotics, prebiotics, synbiotics and fecal microbiota transplantation. Preference was given to systematic reviews, meta-analyses, and randomized controlled trials. Results. Individuals with obesity typically exhibit reduced gut microbial diversity and altered relative abundances of beneficial taxa such as Akkermansia muciniphila and Bifidobacterium longum. Evidence from clinical and translational studies indicates that obesity is associated with decreased microbial diversity and functional alterations affecting short-chain fatty acid (SCFA) production, bile acid metabolism, and inflammatory signaling. Experimental and clinical findings suggest that probiotics and fecal microbiota transplantation (FMT) may improve selected metabolic parameters, although results remain heterogeneous. Moreover, baseline gut microbiota composition may influence the effectiveness of lifestyle and dietary interventions. Conclusions. The gut microbiota plays a significant role in the pathogenesis of obesity and metabolic syndrome. Interventions such as probiotics, FMT, and high-fiber diets show therapeutic potential but require larger, standardized, long-term clinical trials to confirm their efficacy and safety.